THE RELATIONSHIP BETWEEN WORK MOTIVATION AND LEADERSHIP WITH THE PERFORMANCE OF THE STATE CIVIL APPARATUS IN KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI PAPUA BARAT - Ira Elika Bansaleng; Christina Natalina; Fharel M. Hutajulu (Fundamental Management Journal, 2022)
Work motivation and leadership are factors in an effort to improve employee performance in an organization. If the leader provides optimal motivation for his employees, the more optimal the employee's performance in doing his job, but on the contrary, if the motivation given is low, the employee's performance will be low. The purpose of this study was to determine the relationship between work motivation and leadership with the performance of the state civil apparatus in Kantor Wilayah Kementerian Agama Provinsi Papua Barat. The sample in this study was 30 people/respondents from the general secretariat unit and the data were analyzed using Spearman rank correlation analysis. The results of this study indicate that (1) Based on the Spearman rank correlation test, a significance value of 0.000 < 0.05 was obtained, which means that there is a significant relationship between work motivation and performance of the state civil apparatus. (2) Based on the Spearman rank correlation test, a significance value of 0.011 < 0.05 was obtained, which means that there is a significant relationship between leadership and performance of the state civil apparatus. (3) Based on the Spearman rank correlation test, a significance value of 0.000 < 0.05 was obtained, which means that there is a significant relationship between work motivation and leadership with the performance of the state civil apparatus. Which means, if work motivation and leadership increase, the performance of the state civil apparatus will also increase. Keywords: Work Motivation, Leadership, Performance